2018
DOI: 10.1192/bjo.2018.58
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the public on how to provide mental health first aid: narrative review

Abstract: BackgroundExpert-consensus guidelines have been developed for how members of the public should assist a person with a mental health problem or in a mental health crisis.AimsThis review aimed to examine the range of guidelines that have been developed and how these have been implemented in practice.MethodA narrative review was carried out based on a systematic search for literature on the development or implementation of the guidelines.ResultsThe Delphi method has been used to develop a wide range of guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 87 publications
0
32
0
1
Order By: Relevance
“…School of Psychology, Faculty of Health, Deakin University, Burwood, Australia. 5 School of Psychological Sciences, Turner Institute for Brain and Mental Health, Monash University, Clayton, Australia.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…School of Psychology, Faculty of Health, Deakin University, Burwood, Australia. 5 School of Psychological Sciences, Turner Institute for Brain and Mental Health, Monash University, Clayton, Australia.…”
Section: Fundingmentioning
confidence: 99%
“…One factor in MHFA's successful dissemination has been its commitment to evidence-based training and strong research focus [4]. Training courses are based on guidelines on how to provide mental health first aid that are developed using expert consensus studies [5]. Key elements of the guidelines are summarized in a 5-point MHFA Action Plan taught in the course.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth factor is that there is a strong partnership with research. The content of MHFA training has been based on expert consensus guidelines developed using Delphi studies. The experts in these studies have been mental health professionals and people with lived experience.…”
mentioning
confidence: 99%
“…The search settings were adjusted each time to reflect the country of the search engine. Based on previous similar Delphi studies [ 27 ], websites appearing in the top 50 results from each search were reviewed. Previous studies have found that the quality of the resources declines after the first 50 results [ 28 ].…”
Section: Methodsmentioning
confidence: 99%